Proposal for a Demand Forecasting Model for a Company of Industrial Food Equipment (Interdisciplinary Studies Journal, 2024)
In increasingly competitive and dynamic scenarios, where the immediate fulfillment of market needs becomes a competitive advantage, being able to forecast future demand becomes a fundamental element for planning an organization's activities and decision-making. In this context, the present study aims to propose a demand forecasting model to guide the supply chain planning in a company specializing in industrial food equipment. The case study was divided into: qualitative and quantitative data collection, ABC classification and definition of product families to be analyzed, ABC classification and product definition based on the chosen family, analysis of the behavior and characteristics of the time series, definition and application of forecasting models, comparison between projected and actual values, and analysis of results. The study demonstrated that the Holt-Winters method is the appropriate model to be applied, based on the behavior and characteristics of seasonality and trends identified in the data series. The results indicate that, despite differences between the forecasted and actual demand values, the model remains applicable to the organization's reality.
Keywords: Demand Forecasting; Holt-Winters Method; Supply Chain Planning